Molecular identification and amylolytic potential of a thermophilic bacteria species from refuse dump in Ile-Ife, Nigeria - Omoboye, Olumide; Kolawole, Bakare Mufutau; Olusanjo, Adewale Isaac; Olaoluwa, Oyedeji (journal of molecular, 2023)
Molecular identification and amylolytic potential of a thermophilic bacterium species isolated from refuse dump was investigated. Bacte-rial isolates were identified by morphological and biochemical characterization while amylolytic bacterium of interest was identified by molecular analysis using 16S rRNA gene sequencing. The bacterium with the highest α-amylase activity was selected for enzyme pro-duction. The optimal conditions for α-amylase secretion were determined by varying the pH, temperature, percentage soluble starch, nitrogen sources and carbon sources. The isolated and identified bacteria were Bacillus alvei (40%) Bacillus licheniformis (40%) and Bacillus brevis (20%) while Bacillus licheniformis RD24 was identified by 16S rRNA gene sequencing. The peak of amylase production was at 20 h of incubation (925 μg/ml/min). The optimum pH and temperature for the enzyme production were 7 and 45oC respectively. Enzyme production medium with 1% starch gave highest enzyme activity of 102 ± 5.3 μg/ml/min. Peptone gave an enzyme activity of 165 ± 8.97 μg/ml/min and yeast extract gave 52.26 ± 2.86 μg/ml/min. Of the raw starches, cassava flour gave the highest specific activity of 72 ± 0.07 Units/mg proteins, while sorghum starch gave the lowest specific activity of 5 ± 1.52 Units/mg proteins. The study conclud-ed that starch-rich household waste can be employed for amylase production using Bacillus licheniformis RD24